Handbook of mobile ad hoc networks for mobility models - Roy, Radhika Ranjan (Springer, 2011)
The Mobile Ad Hoc Network (MANET) has emerged as the next frontier for wireless communications networking in both the military and commercial arena. Handbook of Mobile Ad Hoc Networks for Mobility Models introduces 40 different major mobility models along with numerous associate mobility models to be used in a variety of MANET networking environments in the ground, air, space, and/or under water mobile vehicles and/or handheld devices. These vehicles include cars, armors, ships, under-sea vehicles, manned and unmanned airborne vehicles, spacecrafts and more. This handbook also describes how each mobility pattern affects the MANET performance from physical to application layer; such as throughput capacity, delay, jitter, packet loss and packet delivery ratio, longevity of route, route overhead, reliability, and survivability. Case studies, examples, and exercises are provided throughout the book. About this handbook: Presents a cutting-edge treatment of the fundamental role mobility models play in analyzing and designing MANET Describes 40 different major mobility models along with numerous associate mobility models and their impact on MANET performances comprehensively Fills a void in commercial, military, and the research arena for multihop mobile ad hoc networking Provides case studies, examples, and exercises throughout the book  ?There has been a wide variety of research in Mobile Ad-hoc Network (MANET) over past many years and there are many models. As the application of wireless technology has grown in recent years in the commercial and military applications, the practitioners and engineers are finding it difficult to make informed choices on how best to apply MANET. This book will provide focus and foundation for these decision makers,comments Dr. Anupam Shah, Chief Engineer of Enterprise & Mission Solutions Business Unit, Science Applications International Corporation (SAIC). Handbook of Mobile Ad Hoc Networks for Mobility Models is for advanced-level students and researchers concentrating on electrical engineering and computer science within wireless technology. Industry professionals working in the areas of mobile ad hoc networks, communications engineering, military establishments engaged in communications engineering, equipment manufacturers who are designing radios, mobile wireless routers, wireless local area networks, and mobile ad hoc network equipment will find this book useful as well.